Design of Web-Based Patient Receivables Collection Information System at RSU Imelda - Hulu, Firdama; Panjaitan, Muhammad Iqbal (Devitara Innovations, 2023)
Utilization of Information Technology (IT) now plays an essential role in the success of an organization's business. By storing information digitally, a company is able to access customer information and process orders quickly. A doctor can immediately give action to the patient after accessing the patient's complete medical record without having to disassemble the paper archives stored in the hospital. This can be done thanks to the existence of a computer-based system that is used to process information, specifically the Management Information System (MIS). Imelda Pekerja Indonesia Hospital is a Type B referral hospital in the city of Medan, North Sumatra, where it often happens that patients are unable to make payments after treatment, both outpatient and inpatient, especially patients who pay for themselves, where every patient who is unable to pay, this is The author makes a patient receivables payment system. Management utilizes the PHP programming language and MySQL database where the patient's receivable data has been recorded by the computer as well as the patient's receivable payment validation process, as for some of the features that exist in this patient receivables information system where patient data input can be done and record of patient receivables.